2018
DOI: 10.1002/ange.201711854
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Oligomers and Fibrils Trapped in a Gel‐like State of α‐Synuclein Assemblies

Abstract: Abstractα‐Synuclein (α‐Syn) aggregation is associated with Parkinson's disease (PD) pathogenesis. In PD, the role of oligomers versus fibrils in neuronal cell death is debatable, but recent studies suggest oligomers are a proximate neurotoxin. Herein, we show that soluble α‐Syn monomers undergo a transformation from a solution to a gel state on incubation at high concentration. Detailed characterization of the gel showed the coexistence of monomers, oligomers, and short fibrils. In vitro, the gel was highly cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…We have also shown that the droplet state can undergo a maturation process into a gel-like state rich in amyloid structure, which is reminiscent of the pathological state seen in Lewy body pathologies [14,15,60]. This phenomenon is expected on the grounds that the transition from the droplet state to the amyloid state takes place through a maturation process, known as Ostwald ripening [61,62], and it is consistent with the recent report that a-synuclein can form hydrogels [63,64]. From a thermodynamic point of view, it is important to note that the gellike assembly is not a stable state in addition to the native, the droplet and the amyloid states, but a slowly evolving conformation on pathway to the amyloid state ( Figure 6A).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have also shown that the droplet state can undergo a maturation process into a gel-like state rich in amyloid structure, which is reminiscent of the pathological state seen in Lewy body pathologies [14,15,60]. This phenomenon is expected on the grounds that the transition from the droplet state to the amyloid state takes place through a maturation process, known as Ostwald ripening [61,62], and it is consistent with the recent report that a-synuclein can form hydrogels [63,64]. From a thermodynamic point of view, it is important to note that the gellike assembly is not a stable state in addition to the native, the droplet and the amyloid states, but a slowly evolving conformation on pathway to the amyloid state ( Figure 6A).…”
Section: Discussionsupporting
confidence: 89%
“…We can thus suggest that the effects of such membranous structures on the ageing process of the droplets involve a slowing down of the amyloid conversion of the gel-like a-synuclein assemblies. This process could create a metastable toxic state, as the gel-like assemblies can be a reservoir for cytotoxic a-synuclein oligomers [64].…”
Section: Discussionmentioning
confidence: 99%
“…For HMF and Syn fibrils, the first 80 and 72 residues out of the starting 98 residues were assigned, respectively ( Figure S4). Similar to previous reports 34 , we observed that for these two fibril forms, the region spanning residues 98-140 was flexible and could not be observed in the crosspolarization (CP) based experiments ( Figure 3, S4 and S5). For HMF, the flexibility of these residues was independently confirmed by INEPT experiments 35 .…”
Section: Structural Differences Between α-Syn Fibril Polymorphs Reveasupporting
confidence: 89%
“…Towards achieving these goals, we present here a straightforward protocol based on centrifugation and filtration procedures, which allows rapid quantitative and qualitative assessment of the different types of α-syn species such as monomers, oligomers and fibrils in samples of different complexities. This protocol is based on years of experience in our group (Fauvet, Mbefo, & Fares, 2012;Khalaf, Fauvet, & Oueslati, 2014) and the evidence that it has been successfully applied in α-syn research by other groups (Ghosh et al, 2015;Kumar, Das, & Mohite, 2018;Zhang, Griggs, Rochet, & Stanciu, 2013).…”
Section: Introductionmentioning
confidence: 99%